Sociology 201/ - Ericksen, Eugene (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course has four objectives, to provide you with understandings of (1) basicmethods of descriptive statistics, like means, medians, quartile spreads, standarddeviations, and skewness, (2) random variation and how different samples selectedfrom the same population may provide different results, (3) the basic idea of statisticalinference, i.e., how we make judgments about what is the population that provided thesample result that we have observed, and (4) how to evaluate possible associations between two variables.